Гібридний метод розв'язування обернених граничних задач теорії потенціалу в частково необмежених областях з тріщиною - Вінтоняк, Н.І.; Хапко, Р.С. (Видавничий дім "Академперіодика" НАН України, 2007)
We consider an inverse boundary-value problem for the crack reconstruction in semiinfinite domains. The numerical solution is realized through the hybrid method. It consists in the iterative procedure, where some functional is minimized on each step of the iteration. The functional is formed from the corresponding nonlinear operator equation. The results of numerical experiments are presented.